Systems and Elements of the IRT T Research Nuclear Reactor. Workshop: educational and methodological manual; учебно-методическое пособие - Naymushin A. G. Artem Georgievich; Ovsenev A. E. Alexander Evgenievich; Kublinsky M. K. Maksym Konstantinovich; Anikin M. N. Mikhail Nikolaevich; Lebedev I. I. Ivan Igorevich; Smolnikov N. V. Nikita Viktorovich (Tomsk, TPU Publishing House, 2025)
Title screen